The spider genus Tutaibo (Araneae, Linyphiidae) in Uruguay: two new species and new records - Cajade, Manuel; Rodrigues, Everton N.L. [UNESP]; Hagopián, Damián; Laborda, Álvaro; Simó, Miguel (Magnolia Press, 2024)
Tutaibo carita Cajade sp. nov. and Tutaibo sam Cajade sp. nov. are described from Uruguay based on males and females. Illustrations of somatic and sexual characters and a species distribution map are provided. In addition, new records of Tutaibo velox (Keyserling, 1886) are provided. These findings represent the southernmost records for Tutaibo and constitute the first report of the genus for Uruguay.
Keywords: Erigoninae; Pampa biome; Taxonomy